\(\dfrac{a^3b^6}{a^3b^2x^5}\)

\(x^6 \div x^4\)

\(x^2\)

\(m^10 \div m^7\)

\(m^3\)

\(y^3 \div y\)

\(y^2\)

\(8x^5 \div 2x^3\)

\(4x^2\)

\(\dfrac{b^8}{b^5}\)

\(b^3\)

\(\dfrac{50m^{16}}{10m^{11}}\)

\(5m^5\)

\(\dfrac{21k^7}{14k^6}\)

\(\dfrac{3}{2}k\)

\(\dfrac{6^2x^3y^3}{2^3x \cdot 3y^5}\)

\(\dfrac{3x^2}{2y^2}\)

\(\dfrac{8a^4}{2a}\)

\(\dfrac{9x^3y}{3xy^2}\)

\(\dfrac{m^2}{\left(n^3\right)^2}\)

Simplify: \(\left(\dfrac{5}{p}\right)^4\)

\(
\left(\dfrac{5}{p}\right)^4 =
\dfrac{5^4}{p^4} =
\dfrac{625}{p^4}\)

Simplify: \(\left(\dfrac{2x}{3}\right)^2\)

\(
\left(\dfrac{2x}{3}\right)^2 =
\dfrac{2^2x^2}{3^2} =\
\dfrac{4x^2}{9}\)

Simplify: \(\left(\dfrac{2mn^3}{3r^2}\right)^3\)

\(
\left(\dfrac{2mn^3}{3r^2}\right)^3 =
\dfrac{2^3m^3n^9}{3^3r^6} =
\dfrac{8m^3n^9}{27r^6}\)

Simplify: \(\left(\dfrac{3x^2}{4}\right)^3\)

\(
\left(\dfrac{3x^2}{4}\right)^3 =
\dfrac{3^3x^6}{4^3} =
\dfrac{27x^6}{64}\)

Simplify: \(\left(\dfrac{-2x^3}{3}\right)^2\)

\(
\left(\dfrac{-2x^3}{3}\right)^2 =
\dfrac{(-2)^2x^6}{3^2} =
\dfrac{4x^6}{9}\)

Simplify: \(\left(\dfrac{3x^3}{9x}\right)^2\)

\(
\left(\dfrac{3x^3}{9x}\right)^2 =
\left(\dfrac{x^2}{3}\right)^2 =
\dfrac{x^4}{3^2} =
\dfrac{x^4}{9}\)

Simplify: \(\left(\dfrac{-4x^4y^2}{6x^2y^2}\right)^2\)

\(
\left(\dfrac{-4x^4y^2}{6x^2y^2}\right)^2 =
\left(\dfrac{-2x^2}{3}\right)^2 =
\dfrac{(-2)^2x^4}{3^2} =
\dfrac{4x^4}{9}\)

Simplify: \(\left(\dfrac{2x^3y^2}{-x^2y^5}\right)^{-2}\)